'Heavenly Beings': Art Facing the Animal in Ljubljana. Issue 2 (4th March 2021) - Smith, Deirdre M
Abstract: Recent exhibitions and publications evidence an increased focus in the artworld on non-human animals. I take this trend as an opportunity to assess the intersection of contemporary art and critical animal studies and posthumanism. I first offer an account of this phenomenon, and put forward an argument for the role art can take in negotiating human–animal boundaries through an analogy between art/non-art and human/animal. I then interpret three artworks included in the exhibition 'Heavenly Beings: Neither Human nor Animal' at the Museum of Contemporary Art Metelkova in Ljubljana, Slovenia in 2018: Franc Purg's Where is the Line? (1998), Maja Smrekar's K-9_topology: Hybrid Family (2016) and Anton Vidokle's Immortality and Resurrection for All! (2017). Focusing on slaughter, interspecies kinship, and life after death, respectively, these artworks are provocative within the meeting of art and animal studies, but have not received sufficient analysis.